O assassinato e a construção da verdade das miudezas de um crime ocorrido em Ponte Alta ao retrato singular de uma criminosa, Mato Grosso (1898) - Paula, Sara Ruth Batista de (2022)
It was August 5, 1898, when Sebastião Julio Soares warned the people with whom he lived and a guest who was at his house that he would make a short trip. This man, owner of a small property called “Ponte Alta”, intended to go to a nearby community, known as Jangada. The trip seemed to be simple, he needed to go to Jangada to pick up an order of brown sugar and hire some men to help him in the fields. He prepared the horse, equipped himself with his sledgehammer and left with the certainty of returning in a short time. He arrived at the intended location without major problems on the way, spent the night at a friend's house. In the morning he walked around the community, saw acquaintances, exchanged a few fingers of conversation and as soon as he picked up his order of brown sugar, he found himself ready to head back to his house. What no one expected is that from that moment on, no one would see Sebastião again, at least not alive. During the course of the investigation assumptions were created, suspects were arrested, but the sentence at the end of the judicial process condemned a man and a woman to 30 years in prison, an emblematic sentence for a case permeated by endless contradictions. Thus, the objective of this research is to investigate the construction of truth in a criminal process, composed of two procedures: police investigation and judicial process. Thus, to deepen the analysis of the construction of truth within the document, I make use of Michel Foucault's theory. The methodological approach, in turn, is carried out through the union and variation between the macro-historical and micro-historical perspectives, seeking to look at the details of the case and, when necessary, expand the scale for society. Finally, in addition to investigating questions of truth, I took as more specific objectives to read between the lines a little more of that society, encompassing social, gender and power relations.